Fractal characteristic analysis of surge impact over shallow underwater vehicle. (2017) - Tang, Zhijie; Liu, Pinglong; Luo, Qian; Luo, Jun; Xie, Shaorong
In the near water surface, the posture control of the underwater vehicle is very important. The underwater vehicle is forced to rotate due to external forces. So, we focus on the surge and the wake flow of thrusters as possible causes of the external forces. Based on fractal dimension concept of fractal theory, the method of short-time fractal dimension is presented to analyse fractal characteristics, focusing on the impact of underwater robot by surge. Respectively, two kinds of surge are introduced: a) surge impacts underwater vehicle from one side; b) surge impacts underwater vehicle from the head. They are analysed every 4s, 2s, 1s and 0.5s. Simulation results show that taking advantage of short-time fractal dimension in underwater vehicle can be dynamically adjusted fuzzy control parameters to improve the posture control of robot under surge.